"Other people's initiatives": exploring mediation and appropriation of place as barriers to community-based climate change adaptation. Issue 11 (2nd November 2017) - Groulx, Mark
ABSTRACT: Adaptation planning at the community level takes on various forms. It generally involves a process of defining climate impacts, vulnerabilities, and actions that can build community resilience. Typically, these processes rely on climate experts and policy-makers to define what is at risk, and therefore what is worthy of investment and protection. Emerging approaches to community-based adaptation-planning advocate for stronger community control over these processes. Drawing on a place-based approach to adaptation, this paper examines place meaning as a co-constructed process. It explores how this process shapes opportunities for community-based climate action in Churchill, Canada. Results indicate that community members acknowledge many competing threats to their sense of place, and suggest that this competition may reduce the perceived need to prioritise climate action to protect connections to place. Results also reveal a concern among community members that local place identity has been appropriated for economic gain, which may further reduce the drive to act in protection of an already exploited sense of place. Overall, findings support calls to adopt place-based perspectives to enhance the capacity of adaptation planning to understand local needs, values, and levers for action.